Domestic Petroleum Price Smoothing in Developing and Transition Countries - Bingham, Benedict (IMF Working Papers; Working Paper ;, 2001)
This paper examines the case for government-led smoothing of domestic petroleum prices in the face of volatile international prices. Governments in most developing and transition countries engage in petroleum price smoothing, as the survey of country practice carried out for this paper shows. This paper reviews the potential welfare implications of petroleum price volatility, and assesses different price smoothing rules on the basis of historical oil prices. These simulations reveal the presence of a sharp trade-off between price smoothing and fiscal stability, suggesting that developing and transition country governments should engage in limited price smoothing and, if possible, rely on hedging instruments to do so.